2017
DOI: 10.1038/srep45519
|View full text |Cite
|
Sign up to set email alerts
|

Three dimensional characterization of GaN-based light emitting diode grown on patterned sapphire substrate by confocal Raman and photoluminescence spectromicroscopy

Abstract: We performed depth-resolved PL and Raman spectral mappings of a GaN-based LED structure grown on a patterned sapphire substrate (PSS). Our results showed that the Raman mapping in the PSS-GaN heterointerface and the PL mapping in the InxGa1−xN/GaN MQWs active layer are spatially correlated. Based on the 3D construction of E2(high) Raman peak intensity and frequency shift, V-shaped pits in the MQWs can be traced down to the dislocations originated in the cone tip area of PSS. Detail analysis of the PL peak dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 37 publications
(39 reference statements)
0
11
0
Order By: Relevance
“…Residual strain can propagate from patterned substrates to induce a wide distribution of In content and QCSE [218]. Therefore, the FWHM behaviors depend on the configuration of the device structures such as growth orientations, design of active regions, patterning of substrates, and dimensions.…”
Section: Spectral Characteristicsmentioning
confidence: 99%
“…Residual strain can propagate from patterned substrates to induce a wide distribution of In content and QCSE [218]. Therefore, the FWHM behaviors depend on the configuration of the device structures such as growth orientations, design of active regions, patterning of substrates, and dimensions.…”
Section: Spectral Characteristicsmentioning
confidence: 99%
“…Time-consuming post-processing, such as Lorentzian lineshape fitting like in this work, is often performed to reduce this 4-D dataset into several more useful 3-D datasets for each property of the peaks of interest. This is the birth of the confocal Raman 3-D imaging technique, which has successfully been utilized in few recent studies [20,[25][26][27]. Optically transparent materials such as α-GaN (and its defects) are particularly suitable for such diffraction-limited volumetric analysis.…”
Section: -D Raman Imaging: Z-stack Representation Of the Biaxial Stre...mentioning
confidence: 99%
“…For instance, the use of their key properties for very promising device applications are hindered by the presence of a high background impurity concentration (in the range of 10 -10 light. Although residual stresses in the as-grown α-GaN single crystals are already well studied by Raman spectroscopy via the peak shift of the main α-GaN Raman modes [18][19][20][21][22] (for at least two decades [23] and also in 3-D [20,21]), only a recent Raman study by N. Kokubo et al (2018) [24] has reported to have utilized Raman 2-D maps to intentionally estimate the TD densities and identify the edge → a -component directions in the material, but none has used the full potential of the confocal Raman microscopy, the diffraction-limited 3-D imaging capability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The residual thermal strain of III–V nitride-based bulk materials can be attributed to the mismatch between the thermal expansion coefficients of GaN and the substrate . The use of a patterned sapphire substrate (PSS) or surface patterning can release the thermal strain of GaN and increase the light extraction efficiency. Similarly, the growth of monolayer TMDC materials generates substrate-induced strain. , The primary reason for the generation of substrate-induced strain is the mismatch between the thermal expansion or reduction of the monolayer MoS 2 crystal lattice and the substrate during the temperature cooling procedure. , The strain distribution of monolayer TMDCs, which are directly placed on a 3-D substrate, is not completely understood. Figure a,b illustrates the schematic of the monolayer MoS 2 fabricated on a flat sapphire substrate (FSS) and a PSS under substrate-induced strain.…”
Section: Introductionmentioning
confidence: 99%